Pre-clinical assessment of SLN360, a novel siRNA targeting LPA, developed to address elevated lipoprotein (a) in cardiovascular disease. (May 2022) - Rider, David A.; Eisermann, Mona; Löffler, Kathrin; Aleku, Manuela; Swerdlow, Daniel I.; Dames, Sibylle; Hauptmann, Judith; Morrison, Eliot; Lindholm, Marie Wikström; Schubert, Steffen; Campion, Giles
Abstract: Background and aims: The LPA gene encodes apolipoprotein (a), a key component of Lp(a), a potent risk factor for cardiovascular disease with no specific pharmacotherapy. Here we describe the pharmacological data for SLN360, a GalNAc-conjugated siRNA targeting LPA, designed to address this unmet medical need. Methods: SLN360 was tested in vitro for LPA knockdown in primary hepatocytes. Healthy cynomolgus monkeys received single or multiple subcutaneous doses of the SLN360 sequence ranging from 0.1 to 9.0 mg/kg to determine the pharmacokinetic and pharmacodynamic effects. Liver mRNA and serum biomarker analyses were performed. Results: In vitro, the SLN360 sequence potently reduces LPA mRNA in primary cynomolgus and human hepatocytes, while no effect was observed on the expression of APOB or PLG . In vivo, SLN360 exposure peaks 2 h after subcutaneous injection with near full elimination by 24 h. Specific LPA mRNA reduction (up to 91% 2 weeks after dosing) was observed with only the 3 mg/kg group showing appreciable return to baseline (40%). No consistent dose- or time-dependent effect on the expression of APOB, PLG or a panel of sensitive markers of liver lipid accumulation was observed. Potent (up to 95%) and long lasting (≥9 weeks) serum Lp(a) reduction was observed, peaking in all active groups at day 21. The minimally effective dose was determined to be 0.3 mg/kg with an ED50 of 0.6 mg/kg. Conclusions: SLN360 induces a sustained reduction in serum Lp(a) levels in cynomolgus monkeys following subcutaneous dosing. SLN360 has potential to address the unmet need of Lp(a) reduction in cardiovascular diseases. Graphical abstract: Image 1 Highlights: Elevated Lipoprotein (a) [Lp(a)] is a potent risk factor for cardiovascular disease. Lp(a) levels are genetically determined; lifestyle changes have no effect on levels. SLN360 is a GalNAc-conjugated siRNA that specifically targets LPA mRNA in the liver. SLN360 induces a persistent and deep reduction in serum Lp(a) in non-human primates. SLN360 can address the unmet need of Lp(a) reduction in cardiovascular diseases.